2019
DOI: 10.1016/j.ymthe.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo PET Tracking of 89Zr-Labeled Vγ9Vδ2 T Cells to Mouse Xenograft Breast Tumors Activated with Liposomal Alendronate

Abstract: Gammadelta T (γδ-T) cells are strong candidates for adoptive immunotherapy in oncology due to their cytotoxicity, ease of expansion, and favorable safety profile. The development of γδ-T cell therapies would benefit from non-invasive cell-tracking methods and increased targeting to tumor sites. Here we report the use of [89Zr]Zr(oxinate)4 to track Vγ9Vδ2 T cells in vivo by positron emission tomography (PET). In vitro, we showed that 89Zr-labeled Vγ9Vδ2 T cells retained their viability, proliferative capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 51 publications
(79 reference statements)
9
109
1
Order By: Relevance
“…Only few studies, however, have addressed the fate of adoptively transferred Vγ9Vδ2 T cells in mice. Although tracing studies suggest in vivo cell survival for periods of at least one to two weeks upon adoptive transfer [146,147], the functional activity of Vγ9Vδ2 T cells re-isolated from tumor bearing mice had vanished over time [147]. Hence, the requirement for high numbers and repetitive administration of human γδ T cells in these models may-at least in part-be ascribed to their limited persistence and functional activity in murine hosts [147].…”
Section: Preclinical Modelingmentioning
confidence: 99%
“…Only few studies, however, have addressed the fate of adoptively transferred Vγ9Vδ2 T cells in mice. Although tracing studies suggest in vivo cell survival for periods of at least one to two weeks upon adoptive transfer [146,147], the functional activity of Vγ9Vδ2 T cells re-isolated from tumor bearing mice had vanished over time [147]. Hence, the requirement for high numbers and repetitive administration of human γδ T cells in these models may-at least in part-be ascribed to their limited persistence and functional activity in murine hosts [147].…”
Section: Preclinical Modelingmentioning
confidence: 99%
“…Aside from the present study on umbilical cord tissue-derived MSCs, 89 Zr-oxine-labelling and PET imaging has also been demonstrated with T-cells, dendritic cells, and bone marrow cells [12, 13, 17, 19]. Together, these studies illustrate the benefits of 89 Zr-oxine labelling: fast implementation, non-invasive tracking over a week post-injection, and interpretation of images un-complicated by the degree of background signal given by the systemically-administered tracers used with nuclear reporter-gene systems [36].…”
Section: Discussionmentioning
confidence: 89%
“…With the introduction of total-body clinical PET scanners this is set to increase by a further ∼40-fold, reducing scan times and radioactive doses for patients and thus increasing the practicality of whole-body cell tracking in the clinic [15]. A handful of preclinical studies have so far shown the worth of 89 Zr-oxine in tracking cell therapies in mouse models, including T-cells [16, 17], dendritic cells, NK cells [13], and bone marrow cells [18, 19]. However 89 Zr-oxine toxicity is dose-dependent and varies between cell types, requiring individual evaluation with each prospective cell therapy prior to clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of human γδ T cells in mice has been mostly examined qualitatively in tumours and other organs such as lymph nodes and spleen by immunohistochemical analysis [7,10,22,23]. Quantitative assessments on whole body and tumour biodistribution of γδ T cells have been studied in syngeneic [24] or xenograft [23] tumour models injecting murine or human γδ T cells, respectively. This work aims to quantitatively compare, and for the first time, the biodistribution profiles of human γδ T cells in immune-compromised mice, implanted with human melanoma A375 Pβ6 tumours at three different locations: subcutaneous (SC), intraperitoneal (IP) or experimental metastatic lung tumours.…”
Section: Ivyspringmentioning
confidence: 99%